Job displacement, family dynamics and spousal labor supply - Martin Halla; Julia Schmieder; Andrea Weber (Johannes Kepler University of Linz, Department of Economics, 2018)
We study the effectiveness of intra-household insurance among married couples when the husband loses his job due to a mass layoff or plant closure. Empirical results based on Austrian administrative data show that husbands suffer persistent employment and earnings losses, while wives' labor supply increases moderately due to extensive margin responses. Wives' earnings gains recover only a tiny fraction of the household income loss and, in the short-term, public transfers and taxes are a more important form of insurance. We show that the presence of children in the household is a crucial determinant of the wives' labor supply response.
Keywords: D19; J22; J65; 330; Firm Events; Household Labor Supply; Intra-household Insurance; Added Worker Effect